2022
DOI: 10.3390/electronics11203291
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Institutions’ Adoption of Artificial Intelligence Applications in Online Learning Environments: Integrating the Innovation Diffusion Theory with Technology Adoption Rate

Abstract: Artificial intelligence applications (AIA) increase innovative interaction, allowing for a more interactive environment in governmental institutions. Artificial intelligence is user-friendly and embraces an effective number of features among the different services it offers. This study aims to investigate users’ experiences with AIA for governmental purposes in the Gulf area. The conceptual model comprises the adoption properties (namely trialability, observability, compatibility, and complexity), relative adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…Within the context of this study, perceived usefulness can be defined as the level to which utilizing a mobile banking application will provide benefits for clients in performing financial transactions [59]. Prior studies [60][61][62][63] have mentioned that perceived usefulness is one of the strongest predictors in the TAM model and has a positive effect on intention to use technology. Studies in e-banking [64,65] have confirmed that perceived usefulness has positive relationship with user intention to adopt e-banking systems.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…Within the context of this study, perceived usefulness can be defined as the level to which utilizing a mobile banking application will provide benefits for clients in performing financial transactions [59]. Prior studies [60][61][62][63] have mentioned that perceived usefulness is one of the strongest predictors in the TAM model and has a positive effect on intention to use technology. Studies in e-banking [64,65] have confirmed that perceived usefulness has positive relationship with user intention to adopt e-banking systems.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…Intelligence stands out as a paramount framework that aids in exploring the assimilation of technology across various domains (Ismail, 2006). A unique benefit of applying this diffusion theory to technology incorporation is its holistic approach, not merely delineating the adoption process but also pinpointing the key factors compelling organizations to embrace AI technology (Almaiah et al, 2022). Pertaining to the current where both entities contribute to decision-making endeavors.…”
Section: Diffusion Of Artificial Intelligence (Ai) Theorymentioning
confidence: 99%
“…The Internet and AI technology are two essential products in the information age. Since birth, they have created and realized many possibilities in various fields [9][10][11][12][13][14][15][16][17][18] . As an excellent tool to improve the concentration of college students, MR shooting games will produce tremendous superimposed efficiency under the blessing of Internet + AI technology and better serve college students 19 .…”
Section: The Stacking Empowerment Effect Of Mr Shooting Games and Ai ...mentioning
confidence: 99%